PHILOSOPHICAL STUDY OF MORAL EDUCATION AND VALUE EDUCATION IN THE FIELD OF EDUCATION - Shukla, Piyush Kumar (International Journal of Research -GRANTHAALAYAH, 2024)
In the present times when the tendencies of materialism, competition, moral degradation and self-centredness are intensifying in the society, the importance of moral education and value education in the field of education has increased more than ever. Not only from the educational point of view, but also from the philosophical point of view, it has become extremely necessary that we should not give only knowledge or technical skills to the future generation, but also provide them the art of living, the conscience of right and wrong, and the sense of social and spiritual responsibility. The aim of education should not be only to give information, but it should become a medium to develop a person as a better citizen, sensitive human being and balanced personality. This is the point where the philosophical basis of moral education and value education becomes extremely important.